2021
DOI: 10.21203/rs.3.rs-916148/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence and Risk Factors for Chronic Postsurgical Pain Following Video-assisted Thoracoscopic Surgery: a Retrospective Study

Abstract: Backgroud: Video-assisted thoracoscopic surgery (VATS) has been widely used as an alternative for thoracotomy, but the reported incidence of chronic postsurgical pain (CPSP) following VATS varied widely. The purpose of this study was to investigate the incidence and risk factors for CPSP after VATS. Methods: We retrospectively collected preoperative demographic, anesthesiology, and surgical factors in a cohort of patients undergoing VATS between January 2018 and October 2020. Patients were interviewed via phon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…Younger patients are biologically more sensitive to low-intensity noxious stimuli and may have higher central nervous system reactivity. Second, from a physiological perspective, older adults are more conservative in pain perception and reporting and are more reluctant to report pain when it occurs [26]. In our study, the effect of age as a determinant factor in patients' pain risk when referring to the pain-free group was observed for both days after multiple adjustment, but the direction of influence seemed not decisive.…”
Section: Discussioncontrasting
confidence: 49%
“…Younger patients are biologically more sensitive to low-intensity noxious stimuli and may have higher central nervous system reactivity. Second, from a physiological perspective, older adults are more conservative in pain perception and reporting and are more reluctant to report pain when it occurs [26]. In our study, the effect of age as a determinant factor in patients' pain risk when referring to the pain-free group was observed for both days after multiple adjustment, but the direction of influence seemed not decisive.…”
Section: Discussioncontrasting
confidence: 49%
“…A large retrospective study on thoracic surgery reported that around 1/3 of patients suffering from CPSP reported moderate or severe chronic pain, but only 3% of patients with CPSP sought active analgesic therapy. 1 In the present study, the incidence of CPSP in patients with and without hookwire localization was 56.5% and 30.4%, respectively, and the incidence was higher (62.9%) in patients undergoing multiple hookwires localization. Nevertheless, most of the patients in our study reported mild-to-moderate pain intensities.…”
supporting
confidence: 41%
“…The incidence of CPSP in thoracic surgery varies from 14% to 83% depending on the type of surgery or the definition of CPSP. [1][2][3][4] CPSP can lead to increased postoperative complications, long-term disability, reduced quality of life, and increased healthcare spending. 5 The development of CPSP is considered a multifactorial process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported to occur in 15% (365/2,396) in one case series and 44% (1,033/2,348) in another with 6.5% (152/2,348) in the moderate to severe range. 55,56…”
Section: Morbidity and Mortalitymentioning
confidence: 99%